General Form of the Power Spectral Density of Multicarrier Signals - R. López-Valcarce (IEEE Communications Letters, 2022)
Multicarrier modulation has been adopted in many modern communication systems because of its many appealing  properties. Its relatively high out-of-band radiation has spurred many techniques to shape the power spectral density (PSD)  of multicarrier signals, including spectral precoding and pulse shaping. We derive a general expression for the PSD which is  valid for subcarrier-specific pulses and for spectral precoders operating over multiple blocks. The only statistical assumptions  on the vector-valued sequence modulating the active subcarriers are wide-sense cyclostationarity and properness. The applicability  of the result to a number of popular multicarrier formats is discussed.
Keywords: rodin; spectrum shaping